The myosin start‐of‐power stroke state and how actin binding drives the power stroke. Issue 10 (13th August 2013) - Preller, Matthias; Holmes, Kenneth C.; Ampe, Christophe; Machesky, Laura M.; Nyitrai, Miklós
<x xml:space="preserve">Abstract</x> We propose that on binding to actin at the start of the power stroke the myosin cross‐bridge takes on the rigor configuration at the actin interface. Starting from the prepower stroke state, this can be achieved by a small movement (16° rotation) of the lower 50K domain without twisting the central β‐sheet or opening switch‐1 or switch‐2. The movement of the lower 50K domain puts a strain on the W‐helix. This strain tries to twist the β‐sheet, which could drive the power stroke. This would provide a coupling between actin binding and the execution of the power stroke. During the power stroke the β‐sheet twists, moving the P‐loop away from switch‐2, which opens the nucleotide binding pocket and separates ADP from Pi. The power stroke is different from the recovery stroke because the upper and lower 50K domains are tethered in the rigor configuration. © 2013 Wiley Periodicals, Inc.